2022
DOI: 10.1007/s00268-022-06645-3
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Outcomes of Critical Traumatic Brain Injury (GCS = 3–5) in a Developing Country: A Retrospective, Registry‐Based Study

Abstract: Background Patients sustaining critical TBI [initial Glasgow Coma Scale (GCS) B 5] generally have poor outcomes. Little is known about the frequency, mortality rate, and functional outcomes of such patients in Iran. Methods In this retrospective, registry-based cohort study, the demographic and clinicoradiological findings of TBI patients were queried from March 21, 2017, to March 21, 2020. We included TBI patients with initial GCS of 3-5. The functional outcome was assessed using the Glasgow Outcome Score-ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 46 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…e previous surveys agreed that younger age is a prognostic factor for improved survival rate. [3] Deng et al reported a decrease in the mortality rate in younger fire-arm-related victims in the US. e mortality rate was 73.3% in patients >60 years of age and 50.2% in patients between 18 and 29.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…e previous surveys agreed that younger age is a prognostic factor for improved survival rate. [3] Deng et al reported a decrease in the mortality rate in younger fire-arm-related victims in the US. e mortality rate was 73.3% in patients >60 years of age and 50.2% in patients between 18 and 29.…”
Section: Discussionmentioning
confidence: 99%
“…[17] e previous studies address several prognostic factors affecting both survival rate and short-to-long-term functional outcomes. [1,3,11] Ambrosi et al reported that preoperative GCS, pupil conditions, and intracerebral hematomas are prognostic factors among patients following GSW. [2] In Austria, Marhold et al analyzed 27 patients with PTBI and concluded that initial GCS, trajectory, type of injury (low-or high-velocity), and pupil status are predictors of functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current assessments for concussion, the most common type of TBI, rely on combining tests designed to evaluate functional domains known to be affected such as balance, memory, and cognition ( 2 ). An individual test for TBI may not be effective in diagnosing a patient if the test has not been designed to assess the specific symptoms with which the patient is presenting ( 3 ).…”
Section: Introductionmentioning
confidence: 99%